Translational Research in Audiology - Szczepek, Agnieszka (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection brings together basic and clinical research papers that cover different topics in audiology but have one thing in common: the translational approach. The research in this collection demonstrates how exciting and interesting translational audiology can be. This collection aims to stimulate interest and encourage more studies of this type.